Study of the chemical composition, proteolysis, lipolysis and volatile compounds profile of commercial Reggianito Argentino cheese: Characterization of Reggianito Argentino cheese. - Wolf, Irma Veronica (2010)
Reggianito is a typical variety of grana-type hard cheese produced in Argentina. It is the most exported and due to its organoleptic characteristics is very appreciated by the consumers. The objective of this study was to characterise the global composition, lipolysis, proteolysis and volatile compound profiles of commercial Reggianito cheeses from different dairy plants. Statistical differences (P 6 0.05) in some physicochemical parameters, nitrogen fractions and FFA levels among commercial brands were detected. The volatile profiles were studied by SPME–GC–MS/FID. A total of 53 compounds were identified, the majority belonging to the groups of ketones, alcohols, acids, esters and aldehydes. All these compounds have been reported in Italian grana-type cheeses. Visualization of the analytical results was performed by principal component analysis. This analysis clustered cheese samples according to dairy plants. This fact could be, among other factors, consequences of differences in technologies and ripening time of different manufacturers.